2a+b-4ab+7-5a+8b=

Simple and best practice solution for 2a+b-4ab+7-5a+8b= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2a+b-4ab+7-5a+8b= equation:


Simplifying
2a + b + -4ab + 7 + -5a + 8b = 0

Reorder the terms:
7 + 2a + -5a + -4ab + b + 8b = 0

Combine like terms: 2a + -5a = -3a
7 + -3a + -4ab + b + 8b = 0

Combine like terms: b + 8b = 9b
7 + -3a + -4ab + 9b = 0

Solving
7 + -3a + -4ab + 9b = 0

Solving for variable 'a'.

Move all terms containing a to the left, all other terms to the right.

Add '-7' to each side of the equation.
7 + -3a + -4ab + -7 + 9b = 0 + -7

Reorder the terms:
7 + -7 + -3a + -4ab + 9b = 0 + -7

Combine like terms: 7 + -7 = 0
0 + -3a + -4ab + 9b = 0 + -7
-3a + -4ab + 9b = 0 + -7

Combine like terms: 0 + -7 = -7
-3a + -4ab + 9b = -7

Add '-9b' to each side of the equation.
-3a + -4ab + 9b + -9b = -7 + -9b

Combine like terms: 9b + -9b = 0
-3a + -4ab + 0 = -7 + -9b
-3a + -4ab = -7 + -9b

Reorder the terms:
7 + -3a + -4ab + 9b = -7 + -9b + 7 + 9b

Reorder the terms:
7 + -3a + -4ab + 9b = -7 + 7 + -9b + 9b

Combine like terms: -7 + 7 = 0
7 + -3a + -4ab + 9b = 0 + -9b + 9b
7 + -3a + -4ab + 9b = -9b + 9b

Combine like terms: -9b + 9b = 0
7 + -3a + -4ab + 9b = 0

The solution to this equation could not be determined.

See similar equations:

| 2x-10=2x+26 | | 2a+b-4a+7-5a+8b= | | n+(n+1)+(n+2)=201 | | 12x-2x=10x-8 | | 4(3x+6)-7=5x-32 | | 8s(s+6)=s-35 | | 10/p=6/9 | | 10-5x=7x-12 | | 8x+4-2x-8= | | 8-63x-8x^2=0 | | -6+5=-72+5x | | 10sin(2x+40)=12 | | 7x+28+8x-48=10x+15 | | 64+5a=-11 | | -8(1-3k)=-128 | | -4(y+8)-5=5 | | 4n=210 | | 5x-1=4x-(2-x) | | 5d-2=14 | | y=88-1.1x | | 0=2x^2-13x-1 | | 2x/5=3/20 | | 2/3=5-2x/9 | | 5451548453+875448435484548X=1223885000 | | 4x+4y=54 | | ×(2/5)=3/20 | | 18x^3-39x^2-24z=0 | | 20+5x=5(x+3) | | 6n-15=-7-2n | | 5a-(1+3a)=2a-1 | | 6y-15=-7y-2y | | 8+2m-6=7m+5-2m |

Equations solver categories